Adsorção do corante amarelo reativo BF-4G 200% por argila esmectita - Rodrigues Filho, Geraldo Martins (2012)
This study aimed to evaluate the potential use of smectite clays for color removal of textile effluents. The experiments were performed by testing exploratory/planning method factorial and fractional factorial where the factors and levels are predetermined. The smectite clays were used originating from gypsum hub of the region Araripe-PE, and the dye used was Reactive Yellow BF-4G 200%. The smectite clay was collected and transported to the Laboratory of Soil Physics of UFRPE, where it held its preparation through air drying, lump breaking and classification in sieve to then submit it to the adsorption process. Upon completion of 22 complete factorial design it was concluded that the values of (96, 96,5 and 95,8%) corresponding to the percentage of of removal for "in-kind", chemically and thermally activated, respectively and adsorbed amounts of (4,80, 4,61 and 4,74 mg/g) for three clays. Showed that the activation processes used did not increase the adsorption capacity of smectite clay. The kinetic data were best fitted to the Freundlich isotherm, with an exponential distribution of active sites and that shows above the Langmuir equation for adsorption of cations and anions by clays. The kinetic model that best adapted to the results was the pseudosecond order model. In the factorial design study 24-1, at concentrations up to 500 mg/L obtains high percentage of color removal (92,37, 90,92 and 93,40%) and adsorbed amount (230,94, 227,31 and 233,50 mg/g) for three clays. The kinetic data fitted well to Langmuir and Freundlich isotherms. The kinetic model that best adapted to the results was the pseudosecond order model